Peran Nabi Muhammad dan Yesus Kristus Dalam Sistem Peradilan Tuhan - Adib, Shohibul (Tasamuh: Jurnal Studi Islam, 2017)
In Christian belief, God’s justice system reflects a perilous justice found in justice in the world. To realize justice in the judicial system of God then acting as a judge is Jesus Christ himself and not God the Father. This implies that in the Christian religion, the role of Jesus Christ so great occupy status as God. At the time, there is no higher authority than Jesus Christ. Who is on trial at the time was everyone from the Christian, Muslim, Buddhist, Hindu and a number of other religions. The main law laid down by Jesus Christ in human judge both of Christianity and non-Christian religions is love and faith in Jesus. It is obvious, that the pressure point is the Christian perspective of love as the main reference for justice law at the time the judge of mankind. From here it would seem that the Christian belief of Jesus Christ seemed to have authority above God the Father and God the Father not only has the power difference as a symbol or symbolic. That is why the Trinity in Christianity is believed to be monotheism. God is three (God the Father, God’s son and the Holy Spirit), but three in a singularity, which is the highest authority in the justice of God in Jesus Christ monopoly. Unlike the case with the Islamic belief system that God later in the justice system that acts as a single judge. The position of Prophet Muhammad can only apply for intercession, pleading for help to God means that man who sought the intercession was forgiven by God. This means that the role of the Prophet Muhammad is no more only as a servant of God and avery long and may not be equated with God’s position. Syafa’at is not necessary for God to grant it. God may grant or deny the intercession of it.